Pengaruh Minat dan Kemandirian Belajar terhadap Hasil Belajar Siswa pada Pembelajaran Matematika secara Daring - Fajar Tirtayasa; Yaya S Kusumah; Suhendra Suhendra (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
Students??? learning achievement cannot be separated from their interest and self-regulated learning. This research aims to analyze the effect of students??? interest and self-regulated learning on their learning achievement in online mathematics learning. The design used in this study is a survey research design with a quantitative approach and descriptive correlational method. The research subjects involved in this study were 30 grade-IX students in one of junior high schools in the city of Bandung, who were selected by using cluster random sampling techniques. Research data were collected through questionnaire, tests, and interviews. Questionnaires are used to obtain data on students??? interest and their self-regulated learning, tests are used to obtain data on students??? learning outcomes, whereas interviews are used to support and strengthen the results of the questionnaire. Data analysis in this study uses regression analysis which requires the fulfillment of the classical assumption test. The results of this study indicate that: (1) the students??? learning interest has a significant effect on their learning achievement in online mathematics learning; (2) the students??? self-regulated learning has no significant effect on their learning achievement in online mathematics learning; and (3) the students??? learning interest and their self-regulated learning have a significant effect on their learning achievement in online mathematics learning.